The Influence of Nationalism Attitude, Institutional Perception, and Trust in Willing to Pay Tax - Sutomo Manan (Golden Ratio of Taxation Studies, 2021)
This research was conducted with the objectives: (1) To analyze the effect of Nationalism Attitudes on Willingness to pay Taxes at KPP Pratama South Makassar (2) To analyze the effect of Institutional Perceptions on Willingness to pay Taxes at the South Makassar Pratama Tax Service Office. (3). To analyze the effect of Trust in Tax Officers on Willingness to pay Taxes at the South Makassar Pratama Tax Service Office. The research method used in this study is descriptive analysis and multiple linear regression analysis, with a total sample of 100 respondents. Based on the results of multiple linear regression analysis, the results show that (1). The attitude of nationalism has a positive and significant effect on the Willingness to pay taxes at the South Makassar Pratama Tax Service Office. (2). Institutional Perception has a positive and significant effect on Willingness to pay Taxes at the South Makassar Pratama Tax Service Office (3). Trust in Tax Officers has a positive and significant effect on Willingness to pay Taxes at the South Makassar Pratama Tax Service Office.